CDC20B is required for deuterosome-mediated centriole production in multiciliated cells - Diego R. Revinski (Nature Portfolio, 2018)
In vertebrate multiciliated cells, most centrioles are synthesized and released by poorly characterized structures called deuterosomes. Here, the authors report that the previously-uncharacterized Cdc20b in mouse and Xenopus associates with deuterosomes and contributes to centriole release.